Pengaruh Literasi Kewirausahaan Dan Literasi Digital Terhadap Minat Berwirausaha Dibidang Start-Up (Studi Pada Mahasiswa Program Studi Manajemen Kosentrasi Kewirausahaan Fakultas Ekonomi Dan Bisnis Universitas Jambi) - Hidayati Hidayati; Besse Wediawati; Novita Sari (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to examine the Effect of Entrepreneurial Literacy and Digital Literacy on Entrepreneurial Interest in The Field of Start-up (Study on Entrepreneurship Concentration Management Students, Faculty of Economics and Business, Jambi University). This research is quantitative and the research data used are primary and secondary data. The population and sample are Students of the Entrepreneurship Concentration S1 Management Study Program, Faculty of Economics and Business, Jambi University, class of 2017-2019, Faculty of Economics and Business, Jambi University, totaling 113 people. Data was collected through the distribution of questionnaires with a Likert scale. The data testing technique uses Validity Test and Reliability Test, R-Square Test and Hypothesis Testing with Bootstrapping using SmartPLS 3.0 Software. The results showed that Entrepreneurial Literacy had a positive and significant effect on Entrepreneurial Interest in the start-up sector, and Digital Literacy had no significant effect on Entrepreneurial Interest in the start-up sector.